PENGARUH ECONOMIC VALUE ADDED DAN MARKET VALUE ADDED TERHADAP RETURN SAHAM (STUDI KASUS PADA SUB SEKTOR SUPERMARKET DAN CONVENIENCE STORE PERIODE 2017-2022) - Sianturi, Agnes Maurice; Jamaluddin (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of Economic Value Added and Market Value Added simultaneously on Stock Returns (Case Study of Supermarket and Mini Market Sub-Sectors for the 2017-2022 Period). The data analysis technique used in this research is descriptive statistical analysis, classical assumption test, panel data regression analysis and hypothesis testing using the Eviews 12 application. The results showed that partially Economic Value Added had no significant effect on stock returns and partially Market Value Added had no significant effect on stock returns. Then simultaneously Economic Value Added and Market Value Added have no significant effect on stock returns. Based on the coefficient of determination, it is found that the contribution of Economic Value Added and Market Value Added in influencing stock returns is very small.